A Study of the Application of New Media and Technology to Innovative Design Education in the Science of Learning - Chen Jiajun; Luo Shiyan; Lai Jiaen; Zhu Leyi; Cai Peijuan; Zeng Jiaying; Zhang Ya (SHS Web of Conferences, 2023)
This paper proposes an innovative design education model that effectively combines learning science theory, new technology, and new media to address the problems of serious homogenisation and disconnection from social requirements in design education. The model is based on the Chinese context, in accordance with the three principles of innovative design education summarized in Tim Brown’s design thinking, and utilizing the learning science theory, new technology, and new media. Analyzing the relationship between learning science theory, new technology, and new media, providing a reference for the full application of new technology and new media in Chinese modern design education, and promoting the application of learning science theory in Chinese modern design education constitute the construction of the model.